2003
DOI: 10.1007/s00266-002-1517-9
|View full text |Cite
|
Sign up to set email alerts
|

Sociological Aspects of Rhinoplasty

Abstract: Although the psychological aspect of the rhinoplasty operation has been a subject of interest for a long time, with the exception of a few studies, sociological factors have been almost totally ignored. In this prospective study the personality characteristics and socioeconomic backgrounds of 216 rhinoplasty patients were evaluated. Between 1994 and 2000, a questionnaire and the Minnesota Multiphasic Personality Inventory (MMPI) were given preoperatively to 157 females and 59 males. The MMPI was also given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 15 publications
7
34
1
2
Order By: Relevance
“…3,9,20,29 In our study most of women were married and housekeeper and in other studies most of women were single, employee and university students. 17,28,30,31 In line with other studies in our study most of women were from families with moderate income.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3,9,20,29 In our study most of women were married and housekeeper and in other studies most of women were single, employee and university students. 17,28,30,31 In line with other studies in our study most of women were from families with moderate income.…”
Section: Discussionsupporting
confidence: 92%
“…Also, these studies showed the higher rate of satisfactions in people after referred to Rhinoplasty compare to other surgeries. 7,17 Studies showed that Body Dysmorphic disorder is the strong predicted factor for tend to cosmetic surgery among people. [18][19] Sørlien T in a study showed that body dysmorphic disorder is defined as a mental confrontation with the imagined defect in appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process, the visual perception of faces is influenced by a complex combination of various factors such as appearance, symmetry and expression [15,20,30,34]. Despite many influential factors, there is universal evidence that all cultures prefer attractive and symmetrical faces [1,17,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the process, the visual perception of faces is influenced by a complex combination of various factors such as appearance, symmetry and expression [15,20,30,34]. Despite many influential factors, there is universal evidence that all cultures prefer attractive and symmetrical faces [1,17,34].Studies have shown that when faces are assessed there is a proportional relationship between symmetry and attractiveness [37], whereby a positive perception is accompanied by greater social acceptance [14]. Attractive adults are seen to have become socially well integrated and they are more often attributed with positive character traits [6,9], revealing that facial appearance has a significant influence on an individual's quality of life.…”
mentioning
confidence: 99%